2021
DOI: 10.3390/genes12020298
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Transcriptional Regulation of Branching Hormonal Signaling Pathways Genes under Drought Stress in Arabidopsis

Abstract: A large number of hormonal biosynthetic or signaling pathways genes controlling shoot branching are widely known for their roles in regulating plant growth and development, operating in synergetic or antagonistic manner. However, their involvement in abiotic stress response mechanism remains unexplored. Initially, we performed an in silico analysis to identify potential transcription binding sites for the basic leucine zipper 62 transcription factor (bZIP62 TF) in the target branching related genes. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The breakthrough is that many of the candidate genes found either in qTNL2-1 or qTNN4-1 are also proposed to be involved in plant stress signaling or response mechanisms. A recent study investigating the transcriptional regulation of hormonal biosynthesis or signaling pathways genes under drought stress conditions, proposed that shoot branching related genes could be involved in the adaptive response mechanisms of plants towards abiotic stress tolerance in Arabidopsis [ 92 ]. We could speculate that under normal growth conditions, plants utilize their resources for their growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…The breakthrough is that many of the candidate genes found either in qTNL2-1 or qTNN4-1 are also proposed to be involved in plant stress signaling or response mechanisms. A recent study investigating the transcriptional regulation of hormonal biosynthesis or signaling pathways genes under drought stress conditions, proposed that shoot branching related genes could be involved in the adaptive response mechanisms of plants towards abiotic stress tolerance in Arabidopsis [ 92 ]. We could speculate that under normal growth conditions, plants utilize their resources for their growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Another group of abiotic stress-responsive genes included stomata closure (drought), heat response transcriptional regulator and temperature sensing and signaling, and CAS (LOC_Os02g49680, extracellular calcium sensor receptor: upregulated in Ilpum but downregulated in NIL) among others. A study conducted by Rolly et al [ 45 ] proposed that phytohormone biosynthesis or signaling pathway genes such as auxin carriers (PIN-FORMED proteins), MAX1–4 (more axillary branching, strigolactone biosynthesis genes), gibberellin biosynthesis genes ( GA20ox1 and 2 ), and cytokinin biosynthesis (isopentenyl transferase, IPT5 and 7 ) could be involved in the adaptive response towards drought tolerance in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the chemical structure of kinetin showed that the formation of its molecule may be the result of the reaction of an adenine residue of DNA with furfural [ 41 ], and recently, furfural was reported to be formed during oxidative damage to DNA in vitro whereas another intramolecular rearrangement yields kinetin in vivo [ 42 ]. In addition, kinetin was found to be the precursor to kinetin triphosphate (KTP), an ATP analog produced upon the salvaging of kinetin by adenine phosphoribosyltransferase (APRT) [ 43 ]; such promising findings led to the investment of more efforts into understanding the cytokinin biosynthesis pathways [ 44 , 45 , 46 , 47 ].…”
Section: Cytokinins Occurrence Structure and Identificationmentioning
confidence: 99%